The Effects of Vaccination Against COVID-19 Incidence: Is the current age-priorities appropriate? - Nugrahari, Dian IP; Hamdah, Nurhanifah (UI Scholars Hub, 2023)
Age is an independent risk factor for COVID-19. Thus, the government of Indonesia prioritizes the elderly and adults with significant comorbidities for COVID-19 vaccination. To discover whether this policy is still appropriate, we evaluated the effects of vaccination against the COVID-19 incidence and infection risk.It was a retrospective cohort study of the NAR COVID-19 and Dashboard KPCPEN COVID-19 of the Depok City Health Department. The tests used to analyze the data were the chi-square and logistic regression tests. We discovered that there was a 92.7% total reduction in the COVID-19 infection rate with vaccination. The infection risk for COVID-19 in vaccinated people aged ≥ 60 years was far lower than those who were unvaccinated (RR = 0.10 vs. 1.72). In conclusion, vaccination reduces the transmission of COVID-19 significantly, especially in the ≥ 60 years age group. It affirms that the age priority policy in the vaccination policy is still applicable and does not require any amendments.